“One of the men who most shaped the history of Istria” - Sukljan, Nejc (Muzikološki zbornik, 2025)
By examining a selection of documents from the Koper archives, this article offers an in-sight into the reception of Tartini in Koper in the nineteenth century. It deals with Luigi Biscontini’s musical treatise Trattatello dell ’Arte del suono e del canto Theoretical and Practical Treatise on the Art of Sound and Singing, the correspondence between Manzoni and Stanco-vich, and documents from the Borisi family collection relating to the erection of the Tartini monument in Piran.
Keywords: 19. stoletje; Koper; nineteenth century; recepcija; reception; Tartini, Giuseppe